An exploration into some dominant features of Filipino social behavior.[article]. - Bonifacio, Manuel Flores
The paper explores some dominant features of Filipino social behavior using a symbolic interactionist perspective. Specifically, the paper attempts to analyze the Filipino's personalism, intrusion, privacy, and submissiveness, and the concepts of success and failure. The analysis predicted on the idea that behavior is to a large extent determined by the sociocultural environment.